Sexual Violence at University: Are Indigenous Students More at Risk? - Dion, Jacinthe (Journal of interpersonal violence, 2022)
University-based sexual violence prevalence is worryingly high and leads to many serious consequences for health and academic achievement. Although previous work has documented greater risk for sexual violence among Indigenous Peoples, little is known about university-based sexual violence experienced by Indigenous students. Using a large-scale study of university-based sexual violence in Canada, the current study aims to (1) examine the risk of sexual violence against Indigenous students compared to non-Indigenous students, and (2) to document sexual violence experiences of Indigenous students. Undergraduate students from six universities (N = 5,627) completed online questionnaires regarding their experience and consequences of university-based sexual violence (e.g., forms of sexual violence experiences, gender, and status of the perpetrator, context of the violence, PTSD, disclosure). Findings indicated that compared with their non-Indigenous peers, Indigenous students experienced significantly higher levels of sexual harassment. However, no difference was found for unwanted sexual behaviors, nor for sexual violence contexts. Among Indigenous students, those having experienced sexual violence after age 18 (outside university) were more likely to report university-based sexual violence. Overall, findings highlight that Indigenous students, as well as non-Indigenous students, experience university-based sexual violence. Given their history, Indigenous students may have different needs, so sustainable policies that foster cultural safety on all campuses are clearly needed.